Synthesis and antimalarial evaluation of novel isocryptolepine derivatives - Whittell, Louise; Batty, Kevin; Wong, R.; Bolitho, Erin; Fox, Simon; Davis, T.; Murray, Paul (Elsevier, 2011)
A series of mono- and di-substituted analogues of isocryptolepine have been synthesized and evaluated for in vitro antimalarial activity against chloroquine sensitive (3D7) and resistant (W2mef) Plasmodium falciparum and for cytotoxicity (3T3 cells). Di-halogenated compounds were the most potent derivatives and 8-bromo-2-chloroisocryptolepine displayed the highest selectivity index (106; the ratio of cytotoxicity (IC50 = 9005 nM) to antimalarial activity (IC50 = 85 nM)). Our evaluation of novel isocryptolepine compounds has demonstrated that di-halogenated derivatives are promising antimalarial lead compounds.